The Effects of Emotional Maturity on Marriage: A Systematic Review - Chairani Najmi; Iswinarti; Yuni Nurhamida (Kirana Publisher (KNPub), 2026)
Early marriage in developing countries presents psychological challenges, particularly regarding emotional readiness. This study examines the role of emotional maturity in marital quality among young couples. Using a Systematic Literature Review (SLR) approach based on PRISMA guidelines, a search was conducted via Publish or Perish on Google Scholar using relevant keywords. Out of 290 articles retrieved, 10 met the inclusion criteria for deep analysis. The findings consistently indicate a significant positive relationship between emotional maturity and marital quality. Mature individuals demonstrate higher adaptability in managing conflicts, role pressures, and household dynamics. Emotional maturity significantly enhances marital satisfaction, harmony, and stability, while lower maturity increases conflict risks. Furthermore, it works synergistically with social support and communication skills. Thus, emotional maturity serves as a crucial psychological prerequisite for a stable and harmonious marriage.